Features of Preclinical Studies of Cell Therapy Products - E. V. Melnikova; M. D. Khorolsky; O. A. Rachinskaya; V. A. Merkulov (Антибиотики и Химиотерапия, 2020)
Preclinical studies are one of the most important stages in the development of drugs for medical use, including cell therapy products (in accordance with the legislation of the Russian Federation — biomedical cell products). Regulatory authorities decide on the possibility of conducting clinical trials in order to bring the medications to the market on the basis of the results of the study of their specific activity and safety. Russian requirements for preclinical studies of cell therapy products generally correspond to foreign ones, the main difference is the need for an expanded program of their conduct. The article analyzes the aspects of preclinical studies (scope, justification of the reduced program, design, animal models used) of some cell therapy products approved for use in medical practice in the United States, the European Union, Japan, and South Korea.